Operation Vengeance : the astonishing aerial ambush that changed World War II - Hampton, Dan (William Morrow, an imprint of HarperCollinsPublishers, 2020)
"...[a] narrative account of the top-secret U.S. mission to kill Isoroku Yamamoto, the Japanese commander who masterminded Pearl Harbor."--